Perimeter security - Arata, Michael J. (McGraw-Hill, 2006)
Perimeter Security has taken on a new level of importance since 9/11. Whether insuring the safety of government buildings, hospitals, residences, or bio-research labs, the safety of workers and materials can only be ensured by outfitting all points of entry with the appropriate alarm and surveillance equipment. This comprehensive hands-on resource focuses on designing, installing, and maintaining perimeter security for buildings